Analgesics Induce Alterations in the Expression of SARS-CoV-2 Entry and Arachidonic-Acid-Metabolizing Genes in the Mouse Lungs - Fatima Khirfan; Yazun Jarrar; Tariq Al-Qirim; Khang Wen Goh; Qais Jarrar; Chrismawan Ardianto; Mohammad Awad; Hamzeh J. Al-Ameer; Wajdy Al-Awaida; Said Moshawih; Long Chiau Ming (MDPI AG, 2022)
Paracetamol and nonsteroidal anti-inflammatory drugs are widely used in the management of respiratory viral infections. This study aimed to determine the effects of the most commonly used analgesics (paracetamol, ibuprofen, and diclofenac) on the mRNA expression of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) entry and arachidonic-acid-metabolizing genes in mouse lungs. A total of twenty eight Balb/c mice were divided into four groups and treated separately with vehicle, paracetamol, ibuprofen, and diclofenac in clinically equivalent doses for 14 days. Then, the expressions of SARS-CoV-2 entry, ACE2, TMPRSS2, and Ctsl genes, in addition to the arachidonic-acid-metabolizing cyp450, cox, and alox genes, were analyzed using real-time PCR. Paracetamol increased the expressions of TMPRSS2 and Ctsl genes by 8.5 and 5.6 folds, respectively, while ibuprofen and diclofenac significantly decreased the expression of the ACE2 gene by more than 2.5 folds. In addition, all tested drugs downregulated (p < 0.05) cox2 gene expression, and paracetamol reduced the mRNA levels of cyp4a12 and 2j5. These molecular alterations in diclofenac and ibuprofen were associated with pathohistological alterations, where both analgesics induced the infiltration of inflammatory cells and airway wall thickening. It is concluded that analgesics such as paracetamol, ibuprofen, and diclofenac alter the expression of SARS-CoV-2 entry and arachidonic-acid-metabolizing genes in mouse lungs.